Science processing skills and science interest among secondary school students in Selangor - Harun, Izzatul Sofia; Azman, Nur Jannah (Journal of Islamic, Social, Economics and Development, 2025)
Secondary schools face a big pedagogical challenge in balancing students' enthusiasm for science and their process abilities. Addressing this issue is crucial for developing a generation capable of understanding and engaging with science. A detailed investigation of this relationship identifies critical issues and suggests opportunities for change. This study explores the relationship between basic science process skills and students' interest in science at one of the secondary schools in Shah Alam, focusing on the core of scientific learning. This study examined two primary questions using quantitative methods: how science process skills vary by gender and age group and how they influence students' interest in science. The target population for this study were all lower secondary students, which includes 50 students from Form 1 and 50 students from Form 2. This study uses a stratified random sampling, and the instrument used for data collection was the Science Process Skills Exam. The results showed no noticeable gender disparities in ability, indicating the broad applicability of these skills for success in science and casting doubt on any potential biases. Age was also not a significant factor, indicating that Form 1 and Form 2 students had similar backgrounds in science. A robust relationship was found between high-interest levels in scientific research and proficient task execution, problem-solving, and critical thinking abilities. The study empowers multiple stakeholders by shedding light on the complex relationships among science process skills, interests, and demographic factors. Teachers can utilize these findings to develop lesson plans, materials, and teaching methods that serve the needs of various students and their scientific curiosity.